Effects of oral treatments on exercise capacity in systemic sclerosis related pulmonary arterial hypertension: a meta-analysis of randomised controlled trials. Issue 6 (27th September 2007) - Avouac, J; Wipff, J; Kahan, A; Allanore, Y
Abstract : Objective: To determine the effects of recently available oral therapies, ie, endothelin receptor antagonists (ERAs) and phosphodiesterase-5 inhibitors (PDEIs), in patients with pulmonary arterial hypertension related to connective tissue disease (CTD), mostly systemic sclerosis (SSc). Method: A systematic literature search was conducted up to April 2007. All randomised controlled trials evaluating the efficacy of bosentan, sitaxsentan and sildenafil vs placebo on exercise capacity were selected. Effect size was calculated in each study to assess the magnitude of treatment effect. Results: In all, 10 studies were analysed, giving a total of 613 participants (186 with CTD) who received the active treatment and 272 (72 with CTD) who received placebo. The effect sizes of bosentan, sitaxsentan and sildenafil for exercise capacity in the CTD subset of patients were non-significant; 0.31 (95% confidence interval (CI) −0.22 to 0.83), 0.26 (95% CI −0.06 to 0.57) and 0.53 (95% CI −0.02 to 0.89), respectively. In the whole PAH population, these values were significant; 0.61 (95% CI 0.38 to 0.84), 0.33 (95% CI 0.15 to 0.51) and 0.58 (95% CI 0.38 to 0.79), respectively. Conclusion: This meta-analysis suggests an absence of clinically relevant improvement on exercise capacity in patients with CTD/SSc after 12 to 18 weeks of treatment. A poor therapeutic response, insufficient power of studies or poor sensitivity to change of the 6-min walk test may explain these results. The promising preliminary data on survival of ERAs and the confounding effects of other comorbidities associated with CTD and SSc may support the latter hypothesis.